Geometric Disproportion of Cardiac Structure and Graft Ischemia Affect Tricuspid Valve Regurgitation Early After Neonatal Heart Transplantation - Asano, Miki; Razzouk, Anees J.; Chinnock, Richard E.; Bailey, Leonard L. (The Annals of thoracic surgery, 2007)
Although tricuspid valve regurgitation (TR) after heart transplantation is a known complication, there has been little discussion of this subject in neonatal heart transplantation. We aim to elucidate the prevalence, etiology, and evolution of TR early after transplant in neonates. Eighty-five neonatal recipients were studied retrospectively by two-dimensional and Doppler echocardiography. The semiquantitative grading of TR was based on the ratio of regurgitation jet area to right atrial area. Immediately after neonatal heart transplantation, TR was recognized in 47 patients (grade 1, n = 18; grade 2, n = 22; grade 3, n = 7; and grade 4, n = 0). Tricuspid regurgitation prevalence diminished from 55% to 19% with reduction in severity 1 year after transplantation. The prevalence of TR (grade 2 and grade 3) was affected by a donor/recipient body weight ratio of more than 2.0 ( p = 0.004) and graft ischemia for more than 3 hours ( p = 0.014). The ratio of donor and recipient right atria portion, which had a correlation with donor/recipient body weight ratio (r 2 = 0.415, p < 0.0001), separated the four subgroups in terms of TR grade immediately after transplantation ( p = 0.0064) and also at 1 year after transplantation in all surviving grafts from 1.48 ± 0.54 to 0.8 ± 0.32 ( p < 0.0001). The Cox model found no significance for early posttransplant TR as a risk factor for graft survival. Early posttransplant TR was affected by atria geometrical disproportion and by graft ischemia. Tricuspid regurgitation was not a risk factor for graft survival because of its amelioration over time, perhaps induced by recipient growth and recovery of myocardial injury relating to graft procurement.